(untitled) (Desenvolvimento em Questão, 2025)
Since colonization, the Amazon has been the scene of projects by “outsiders” who see this territory simply as a reserve of value due to its natural and human characteristics, a “territorial fund” of capital [still] fully exploited. As a result of the successive regimes of expropriation applied to the Amazon region over centuries, the region also presents the highest levels of rural violence in Brazil, both symbolically and materially, as an excellent “frontier.” The victims of these violent regimes are often people who are members of social movements, groups of indigenous villages, rural settlements, quilombolas, artisans, fishermen, representatives of various categories. In this sense, this work not only discusses the frontier in the Amazon, but also focuses on the political violence that exists in border regions, with a focus on women. Thus, this work aims to discuss political violence on the Amazon borders characterized as a political death, particularly an attempt to eliminate political forms led by women, a politics associated with life destroyed by someone’s death and the reproduction of common goods, by a distinctly male pioneering spirit. In terms of methodological aspects, this article will consider the completion of a bibliographical research, from an interdisciplinary perspective, of different authors who deal with the proposed theme, delving into different fields of knowledge, such as sociology, anthropology, geography and law. In this sense, the erasure of the Amazonian borders allows us to rethink the border as a concept of the human condition and not simply a spatial condition of dispossession.